2017
DOI: 10.1186/s13071-017-2381-4
|View full text |Cite
|
Sign up to set email alerts
|

γ-Carboxymuconolactone decarboxylase: a novel cell cycle-related basal body protein in the early branching eukaryote Trichomonas vaginalis

Abstract: Backgroundγ-Carboxymuconolactone decarboxylase (CMD) participates in the β-ketoadipate pathway, which catalyzes aromatic compounds to produce acetyl- or succinyl-CoA, in prokaryotes and yeast. Our previous study demonstrated that expression of a CMD homologue that contains two signatures (dualCMD) is negatively regulated by iron in Trichomonas vaginalis. However, we were not able to identify the components of the β-ketoadipate pathway in the parasite’s genome. These observations prompted us to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…In fact, the trophozoite population exhibited an average of 67.3% ± 5% cells in the G1 phase, 23.3% ± 5.3% cells in the S phase, and 9.3% ± 1.8% cells in the G2/M phase (Figure C), whereas pseudocysts exhibited an average of 48.8% ± 3.6% cells in the G1 phase, 25% ± 0.9% cells in the S phase, and 26.1% ± 3.4% cells in the G2/M phase (Figure C). Thus, our results agree with those previously reported that show a positive correlation between the G2/M phase and CMD1 abundance in T. vaginalis cultivated in conditions of iron depletion . Since CDM1 has been located in the basal body of the parasites, and its mRNA and protein abundance are modulated during cell cycle, this protein has been associated with the regulation of cell cycle progression, particularly cytokinesis .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In fact, the trophozoite population exhibited an average of 67.3% ± 5% cells in the G1 phase, 23.3% ± 5.3% cells in the S phase, and 9.3% ± 1.8% cells in the G2/M phase (Figure C), whereas pseudocysts exhibited an average of 48.8% ± 3.6% cells in the G1 phase, 25% ± 0.9% cells in the S phase, and 26.1% ± 3.4% cells in the G2/M phase (Figure C). Thus, our results agree with those previously reported that show a positive correlation between the G2/M phase and CMD1 abundance in T. vaginalis cultivated in conditions of iron depletion . Since CDM1 has been located in the basal body of the parasites, and its mRNA and protein abundance are modulated during cell cycle, this protein has been associated with the regulation of cell cycle progression, particularly cytokinesis .…”
Section: Resultssupporting
confidence: 93%
“…In addition, we observed in pseudocysts a significant 50-fold increase in the abundance of 4-carboxy­muconolactone decarboxylase family protein 1 (CMD1) (Figure A). It has been shown that CMD1 expression is induced by different stress conditions, such as iron depletion, cold treatment, and glucose restriction. ,, It has also been recently observed that parasites cultivated under conditions of iron depletion exhibited a substantial increase in CMD1 expression concomitant with a reduction of cells in the G1/S phase and an increase in the number of cells in the G2/M phase . Thus, we assessed the cell cycle of trophozoites and pseudocysts to determine the proportion of cells in each stage.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The genomes of two novel strains were analyzed extensively. The genome A5410 harbored some important unique genes, such as transporter proteins, endonuclease protein, phage tail protein, aspartate/glutamate racemase family protein arsD gene involved in arsenic resistance ( Firrincieli et al, 2019 ), and the carboxymuconolactone decarboxylase protein involved in protocatechuate catabolism ( Cheng et al, 2017 ). The nitrogen fixation gene cluster was only present in the A5410 strain isolated from pineapple ( Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
“…The nitrogen fixation cluster was also present in D. solani and P. atrosepticum ( Bell et al, 2004 ; Golanowska, 2015 ). Carboxymuconolactone decarboxylase participates in the catalysis of aromatic compounds to produce acetyl- or succinyl-CoA in prokaryotes and yeast ( Cheng et al, 2017 ). Carboxymuconolactone decarboxylase was present in Azotobacter vinelandii, Acinetobacter calcoaceticus , and Pseudomonas putida ( Yeh et al, 1981 ).…”
Section: Discussionmentioning
confidence: 99%